The Effects of Teaching Human and Social Sciences in A Training Program Intended for Physical Education Students in Tunisia - Nasri, Bechir; Souid, Ines (Advances in Social Sciences Research Journal, 2024)
This research addresses the question of the social representation of human sciences teaching in a training program intended for physical education student trainees. The objectives of the study are to identify the social representations of human sciences teaching for student trainees and to see the influence of social representation on practice[1]and educational behaviors. Data was collected through in-depth interviews using an associative method with a representative sample of students. The results show that the participants’ social representation of the human sciences is organized around common elements: the understanding of human beliefs, life and culture.